Penerapan Model Pembelajaran Problem Based Learning Berbantuan Media Vidio Untuk Meningkatkan Hasil Belajar Siswa - Anggraeni, Amelia Tri; Afriza, Edi Fitriana; Kurniawan, Kurniawan (PUSDATIN Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2024)
The problem in the study is the low learning outcomes of students in economic subjects in class XI SMA Negeri 2 Singaparna. The research was conducted to determine the effectiveness of the application of the Problem Based Learning learning model assisted by video media in improving the learning outcomes of students in the economic subject of class XI SMA Negeri 2 Singaparna in the 2024/2025 academic year. The study used a quasi-experimental method with a Nonequivalent Control Group Design design. The population was 247 consisting of 8 classes, using purposive sampling technique, the sampling was determined as many as 2 classes including XI-5 (experimental group) while XI-8 (control group). The data collection technique used was conducting a Pretest and Posttest consisting of 25 items with alternative multiple choice answers. Based on the results of the study, it is explained that there is a significant difference in the improvement of student learning outcomes using the Problem Based Learning learning model assisted by video media on labor material, where the average posttest value is superior to the average posttest value using the conventional model, thus it can be concluded that the Problem Based Learning learning model assisted by video media can improve student learning outcomes.